Beak Trimming by Infrared Radiation of Layers - Pelicia, K.; Garcia, E. A. [UNESP]; Santos, T. A. [UNESP]; Santos, G. C.; Vieira Filho, J. A. [UNESP]; Silva, A. P.; Moreira, J.; Rabello, C. B.; Garcia, R. G. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2019)
This study aimed at evaluating beak-trimming methods and intensities on the performance, beak length and uniformity, and egg parameters of commercial layers. During the rearing period, birds were distributed in randomized blocks, with a 2x3 factorial design + two treatments, consisting of beak trimming with infrared (IR) radiation (moderate or severe); three IR intensities (low: 42 nm, intermediate: 46 nm, or high: 52 nm); and two control hot blade (HB) beak trimming treatments (moderate or severe) with eight treatments and five replicates of 21 chicks each, totaling 840 birds. During the growing phase (second experiment) the factorial design was modified to 2 x 3 x 2 + 4, comprising two IR beak-trimming intensities (moderate or severe); three IR radiation intensities (low, moderate and high), second beak trimming at 11 weeks of age or not, and four additional HB beak trimming treatments (moderate or severe) beak-trimming intensities, and second beak trimming at 11 weeks of age or not. There were 6 treatments with six replicates of seven birds each, totaling 672 laying hens, out of which 576 were selected for evaluation during the production period, with the same number of treatments and replicates of the previous phase. Weight gain (g), body weight (g), body weight uniformity (%), beak length (mm) and uniformity (%), absence of cannibalism (%), livability (%), egg production (%), feed intake (g), feed conversion per eggmass, eggmass, specific gravity, eggshell strength, Haugh unit, % yolk were evaluated. Beak trimming by infrared radiation may be employed in commercial laying hens.
Keywords: Alternative beak-trimming methods; beak-trimming; infrared radiation; Lohmann White layers